Crambescin C1 Acts as A Possible Substrate of iNOS and eNOS Increasing Nitric Oxide Production and Inducing In Vivo Hypotensive Effect - Rubiolo, Juan A.; Lence, Emilio; González-Bello, Concepción; Roel, María; Gil-Longo, José; Campos-Toimil, Manuel; Ternon, Eva; Thomas, Olivier P.; González-Cantalapiedra, Antonio; López-Alonso, Henar; Vieytes, Mercedes R.; Botana, Luis M. (Frontiers in Pharmacology, 2021)
Crambescins are guanidine alkaloids from the sponge Crambe crambe. Crambescin C1 (CC) induces metallothionein genes and nitric oxide (NO) is one of the triggers. We studied and compared the in vitro, in vivo, and in silico effects of some crambescine A and C analogs. HepG2 gene expression was analyzed using microarrays. Vasodilation was studied in rat aortic rings. In vivo hypotensive effect was directly measured in anesthetized rats. The targets of crambescines were studied in silico. CC and homo-crambescine C1 (HCC), but not crambescine A1 (CA), induced metallothioneins transcripts. CC increased NO production in HepG2 cells. In isolated rat aortic rings, CC and HCC induced an endothelium-dependent relaxation related to eNOS activation and an endothelium-independent relaxation related to iNOS activation, hence both compounds increase NO and reduce vascular tone. In silico analysis also points to eNOS and iNOS as targets of Crambescin C1 and source of NO increment. CC effect is mediated through crambescin binding to the active site of eNOS and iNOS. CC docking studies in iNOS and eNOS active site revealed hydrogen bonding of the hydroxylated chain with residues Glu377 and Glu361, involved in the substrate recognition, and explains its higher binding affinity than CA. The later interaction and the extra polar contacts with its pyrimidine moiety, absent in the endogenous substrate, explain its role as exogenous substrate of NOSs and NO production. Our results suggest that CC serve as a basis to develop new useful drugs when bioavailability of NO is perturbed.